2014
DOI: 10.3109/08990220.2014.908837
|View full text |Cite
|
Sign up to set email alerts
|

The impact and specificity of nerve perturbation on novel vibrotactile sensory letter learning

Abstract: The purposes of this study were to determine if induced radiating paresthesia interferes with (a) acquisition and/or (b) utilization of complex tactile information, and (c) identify whether interference reflects tactile masking or response competition. Radiating ulnar (experiment 1) and median (experiment 2) nerve paresthesia was quantified on ulnar innervated vibrotactile Morse code letter acquisition and recollection tasks. Induced paresthesia differentially impacted letter acquisition and recollection, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…These studies (Verrillo & Bolanowski, 1996;Zhang et al, 2009) suggest that a stimulus which occurs during the acquisition of tactile information may provide improvement to knowledge transfer. Another study which is in line with these findings is a study by Passmore et al (2009). Passmore et al (2009) had participants attempt to recreate the components of Morse code patterns and found that when paresthesia stimulation was present under transfer conditions, performance was significantly better than for the no-stimulation group (Passmore et al, 2009).…”
Section: Reaction Timementioning
confidence: 64%
See 2 more Smart Citations
“…These studies (Verrillo & Bolanowski, 1996;Zhang et al, 2009) suggest that a stimulus which occurs during the acquisition of tactile information may provide improvement to knowledge transfer. Another study which is in line with these findings is a study by Passmore et al (2009). Passmore et al (2009) had participants attempt to recreate the components of Morse code patterns and found that when paresthesia stimulation was present under transfer conditions, performance was significantly better than for the no-stimulation group (Passmore et al, 2009).…”
Section: Reaction Timementioning
confidence: 64%
“…Another study which is in line with these findings is a study by Passmore et al (2009). Passmore et al (2009) had participants attempt to recreate the components of Morse code patterns and found that when paresthesia stimulation was present under transfer conditions, performance was significantly better than for the no-stimulation group (Passmore et al, 2009).…”
Section: Reaction Timementioning
confidence: 64%
See 1 more Smart Citation
“…In addition, Passmore (2014) had participants recreate the components of Morse code patterns and found that when paresthesia stimulation was present under transfer conditions, performance was significantly better than for the no-stimulation group. These results indicate that a secondary stimulus may draw increased attentional resources toward discerning the meaningful stimulus (Mendez-Balbuena et al 2012, 2015Passmore 2014). Cognitive load studies confirm that under high-load conditions there is decreased activation in brain regions associated with emotion (amygdala) and increased activation in executive control areas (prefrontal cortex) (Erthal et al 2005;Okon-Singer et al 2007;Van Dillen et al 2009).…”
Section: Behavioral Datamentioning
confidence: 94%
“…Another method to alter somatosensory feedback is to induce paresthesia using transcutaneous nerve stimulation to impair somatosensory inputs [ 23 , 24 , 25 ]. Paresthesia can be induced by transcutaneous electrical stimulation applied over the estimated path of the chosen peripheral nerve [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%